2019
DOI: 10.1007/978-3-030-20503-4_42
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Testing of Visual HMIs for Merging of Trucks

Abstract: Merging sections are challenging for drivers of heavy goods vehicles. Visual support for merging was evaluated in a simulator. Experiment 1 tested HMIs that provided participants (n = 5) driving on the on-ramp with a top view or various forms of speed advice for accelerating behind or in front of a truck platoon on the freeway. Experiment 2 tested HMIs that provided drivers (n = 18) on the acceleration lane with a top view complemented with speed and gap advice for finding a gap to merge in. Experiment 1 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Zhu et al, 2022), and the presence of heavy goods vehicles in merging (e.g. Dreger et al, 2020;Sharma et al, 2020). Future research could also focus on the development of feedback and cooperative systems that support the merging/lane change decision (e.g.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al, 2022), and the presence of heavy goods vehicles in merging (e.g. Dreger et al, 2020;Sharma et al, 2020). Future research could also focus on the development of feedback and cooperative systems that support the merging/lane change decision (e.g.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Future research could also focus on the development of feedback and cooperative systems that support the merging/lane change decision (e.g. Ali et al, 2020;Dreger et al, 2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Blomdahl (2016) raised concerns about impaired communication of drivers to other road users through CMS compared to current mirrors, because of the fixed field of view. Dreger et al (2020) found that drivers can be cognitively overloaded with visual ADAS, reducing the potential benefits of driver aids. Actual support for identifying road users' intentions is not foreseen using either classical mirrors or CMS.…”
Section: Recommendations For Future Merging Support and Automationmentioning
confidence: 99%